A situação atual do trabalho juvenil: a juventude e as exigências sociais para o seu ingresso no mercado de trabalho - Oliveira, Tiago Lopes de (2008)
The present research is focused on contributing to the process of reflection regarding contemporary means of inclusion of youngsters in the labor market, having as its objective the analyses of the influence of such means of inclusion in the life of youngsters in general, especially with regard to their possibilities of development and resistance to the social control mechanisms. The study is based on the description of the means by which the insertion of youngsters in the labor market occurs, as well as on the discussion over the meaning of labor itself nowadays, containing furthermore an analyses of a program of insertion of youngsters in the labor market, known as the School Company Integration Center - SCIC. In order to raise data related to the object of this study, information has been collected from legal documents, statistic researches and theoretical concepts of both national and international authors. An enquiry has also been elaborated and then answered by an SCIC officer, in order to allow us to have a deeper understanding on how such program of insertion of youngsters in the labor market works and how is influences the life of youngsters in general. In order to base the analyzes brought by this research, we have privileged principally the concepts of work developed by Marx and Marcuse, as well as the concepts of industrial society, formation and ideology exposed by Adorno, Horkheimer e Marcuse, all authors of the Criticism Theory. We have learned that in the capitalist society of nowadays the inclusion of youngsters in the labor market serves directly the interests and objectives of the market and its players, not contributing to the development of the individual itself. Moreover, we have realized that the motives that lead youngsters to the labor market are utterly the necessity of making a living and gaining professional experience for future jobs/functions. Regarding how the inclusion in the labor market influences youngsters, its is important to emphasize that the juvenile worker is also subject to the implications and demands imposed by the market of capitalist production, in which the work is a social control mechanism. In conclusion, we have understood that the work leads youngsters to learn and adapt to a model of behavior that does not favor the development of attitudes of standalone thinking, serving in fact the interests of corporations